Medium and large mammal richness from the marine and coastal wildlife refuge of Pacoche, Ecuador - Lizcano, Diego J.; Cervera, Laura; Espinoza-Moreira, Sueanny; Poaquiza-Alava, Diana; Parés-Jiménez, Violeta; Ramírez-Barajas, Pablo J. (THERYA, 2015)
Introduction: Ecuador is a megadiverse country with high endemism rates. However, very few studies describe the diversity and abundance of medium and large mammals in protected areas of the coast. In this work we carried out the first inventory of medium size and large mammals for the marine and coastal wildlife refuge of Pacoche (RVSMCP) in Ecuador. Methods: 60 camera traps were located with one kilometer separation, the cameras were active between 30 and 45 days to carry out an inventory of medium and large sized mammals in the RVSMCP. Results: We found 16 wild mammal species and seven domestic animals in the RVSMCP. The most abundant species were Cuniculus paca, Dasypus novemcinctus and Eira barbara. Odocoileus virginianus was the largest mammal. In addition, we report some notable records of Cebus aequatorialis and Alouatta palliata feeding on fruits on the ground. Discussion and conclusions: The RVSMCP is a young protected area in the coastal region of Ecuador with a unique mammal diversity, protecting species such as the endangered monkeys Cebus aequatorialis and Alouatta palliata in addition to the Guayaquil’s squirrel, Simosciurus stramineus, almost endemic and poorly studied. The RVSMCP represents an opportunity to develop mammal conservation projects in a region poorly studied.